The Influence of Work Environment, Organizational Culture, and Motivation on the Performance of Soldiers in Yonarmed 19/105 Tarik Bolaang Mongondow - I Gede Bagus Tomy Supraja; Asep Kurniawan (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2025)
Being a TNI AD soldier is required to always carry out an ideal performance, because it will affect the performance of the organization in this case, Private Yonarmed 19/105. Problems that often arise related to performance in Yonarmed 19/105 is the low performance of soldiers. The purpose of this study was to determine the description and influence of the work environment, organizational culture and motivation on performance. The research method uses quantitative methods with descriptive analysis. The research sample was 89 respondents with simple random sampling technique. The results of the descriptive analysis of the work environment are categorized as very high, organizational culture is categorized as very high, work motivation is categorized as very high, and performance is categorized as high. The results showed that partially or simultaneously there is an influence of work environment, organizational culture and work motivation on performance. So it can be concluded that a comfortable work environment, good organizational culture and providing periodic motivation can improve the performance of soldiers on duty in the Yonarmed 19/105 unit.